ANALISIS PENGENDALIAN BANJIR DI KAWASAN ENTROP DISTRIK JAYAPURA SELATAN, KOTA JAYAPURA - Agung Sampebua; Apolo Safanpo; Harmonis Rante (Jurnal ELIPS (Ekonomi, Lingkungan, Infrastruktur, Pengembangan Wilayah, dan Sosial Budaya), 2021)
This study aims to analyze the causes, countermeasures and strategies to prevent flooding in the Entrop area, South Jayapura District, Jayapura City. Data collection was carried out by observation, interviews and secondary data retrieval. The analysis was carried out using quantitative and qualitative methods. The results showed that the cause of flooding in the Entrop area was the conversion of forest functions for agricultural activities and settlements, bad habits of the people throwing garbage into the river, the physical characteristics of the flat and watertight area, tides in the river mouth, disruption of the river basin, drainage in front of CV. . Tomas has small dimensions, the tunnel that was built is not functioning properly, the Suzuki front drainage is narrow and is a closed channel, the water channel to Youtefa Bay is only two, the river flow in SMA 4 turns and then returns to the front drainage of CV. Thomas, narrowing of the river cross-section by settlements that are built too close to the river flow and the road along Entrop is low elevation. Flood prevention strategies in the Entrop Area, covering various aspects including environmental aspects, technology and information, evaluation and monitoring, and Regional Spatial Planning.